Comparison of two software programs used to determine the relative supersaturation of urine ions - Anthony, Reshma M.; Davidson, Stephen; MacLeay, Jennifer M.; Brejda, John; Werness, Peter; Jewell, Dennis E. (Frontiers in Veterinary Science, 2023)
Relative supersaturation (RSS) values for urine ions can predict the risk of urinary bladder stone formation. In order to calculate RSS in pets, computer programs developed to measure RSS in human medicine have been adapted to veterinary medicine. However, older programs have not been updated for use in animals, and the early freeware programs for RSS calculations can no longer run with current hardware and operating systems. One of the first RSS programs was developed in BASIC computer language in 1985 and was called EQUIL2. The EQUIL2 program was updated to a compiled version compatible with a PC platform, but the formulas could not be read or altered. This study evaluates a program with known coefficients to the original EQUIL2 program. The predictive abilities of EQUIL2 were measured and compared through calculating an r2 from correlation analysis and by a Bland-Altman analysis of outputs from the two programs using urine samples from healthy dogs and cats. Our results show that for both magnesium ammonium phosphate (struvite) and calcium oxalate, the RSS values were comparable. Although the actual RSS values were different (as might be expected through the use of the updated coefficients) the results were highly correlated, finding elevations and reductions in RSS in the same urine samples. Thus, these two RSS programs find similar differences between samples. However, the actual RSS value may not produce identical results, most likely arising from different thermodynamic stability constants in the calculations. The current work creates a foundation for using the modernized program to calculate RSS and provides a shared method to calculate RSS across the veterinary community.